EFEKTIFITAS PERMAINAN BALOK HURUF UNTUK MENINGKATAN KEMAMPUAN MENGENAL HURUF KONSONAN PADA ANAK TUNAGRAHITA RINGAN (Single Subject Research Kelas III C di SLB Negeri 2 Padang ) - Silfi Sutri Insani (Jurnal Penelitian Pendidikan Khusus, 2014)
This researck was conducted due to a  student with light mental retardation in class III of SLBN 2 padang got difficulties in recognizing consonant letter (b) found in the beginning, in the middle and at the end of a world. Therefore, this research was intended to improve the student’s ability in the recognizing consonant letter (b) by using letter block game. The observation was done in three session. First, the baseline session (A) consisting of five times of observations in which to percentage of the student’ ability in recognizing consonant letter (b) in the beginning of a world was between 0% to 40% while the ability recognizing the letter in the middle of a world was 0%, and the ability to recognize the letter of the end of a world was 0%. Second, the intervention session (B) consisting of 8 times of observation in week the percentage of the student’s ability in recognizing consonant letter (b) in the beginning of a world was between 40% to 80% while the ability to recognize the letter in the middle of a world was between 20% to 69%, and the ability to recognize the letter of at the end of a world was between 20% to 60%. Third the baseline session (AA) consisting of five times of observation in which the percentage of the student’s ability in recornizing consonant letter (b) in the beginning of a worls was between 20% to 80% while the ability to recognize the letter in the middle of a world was between 20% to 60% and the ability to recognize to latter of the end of a worldf bêtween 20% to 40%. Based on these result, it was concluded that the use of latter block game could improve the  ability of the student with light mental retardation in recognizing consonant letter (b) in the beginning, im the middle and at the end a words in class III of SLBN 2 Padang.